Bioactive Profile Analysis and Inhibitory Activity of Prostaglandin Synthase from Sungkai Leaf Extract (Peronema canescens Jack) In Silico - Hasibuan, Muhammad Marsha Azzami; Andrianto, Dimas; Setiarto, Raden Haryo Bimo (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Sungkai leaves (Peronema canescens Jack) have antipyretic properties that have been proven ethnobiologically. However, research on sungkai leaves is scarce, especially in silico and in vitro. The aim of this study was to prove the ability of sungkai leaves to accelerate the process of decreasing body temperature during fever using the silico method. Sungkai leaves were extracted using a 70% ethanol solvent. The extract solution was concentrated using a rotary evaporator and then analyzed using an LC-MS device. Compounds obtained from the LC-MS analysis were screened in silico using Lipinski's rule of 5 and ADMET. The compounds that successfully passed the screening were docked with the target enzyme mPGES-1 using the Yasara Structure application. Extraction with 70% ethanol solvent resulted in an extract yield of 14.75%. The results of the LC-MS analysis showed the presence of 22 known compounds and one unknown compound. The screening results showed that ten compounds had successfully passed. Compounds 2-oxo-6-(piperidine-1-sulfonyl)-benzoxazole-3-carboxylic acid isobutyl ester; 2-(5-{[Isopropyl (methyl)amino] methyl} – 1 - tetrazolidinyl) – N – methyl – N - [ 2 - ( 2 – methyl – 1 – imidazolidinyl) ethyl] acetamide; 2-({2-[4-(2-Hydroxyethyl)-1-piperazinyl]-2-oxoethyl} sulfanyl)-5,6-dimethylthieno[2,3-d]pyrimidin-4(3H)-one;2-({4 amino -5-[3-(diethylsulfamoyl) phenyl]-4H-1,2,4-triazol-3-yl}sulfanyl)-N-dimethylacetamide; and 3, 4,5-trimethoxycinnamate obtained from this study could inhibit mPGES-1 based on the binding energy and inhibition constant that each test ligand had.